Development of Integrated Flipbook Learning Media with 2-Dimensional Quartet Cards (KAKASIBOOK) to Improve Student Learning Outcomes in IPAS Learning Content - Restu Eri Yulianti; Barokahah Isdaryanti (Postgraduate, University of Mataram, 2025)
This study used a research and development method (Research and Development) referring to the Borg and Gall model. This study was conducted with the aim of developing and testing the feasibility, practicality and effectiveness of the Kakasibook learning media. This study involved 26 students with 6 students as small-scale trial subjects and 20 students as large-scale trial subjects of SD Negeri Gondoriyo. The data collection techniques used were test techniques (pretest-posttest) and non-tests in the form of observation results, questionnaires, interview results and document data. The validation results were carried out by media expert validators and material experts which showed that the Kakasibook learning media had met the valid criteria with a score of 90% by the media expert validator, and 95% by the material expert validator. Based on the pretest-posttest results, it is known that Kakasibook is effective in improving student learning outcomes as evidenced by the results of an increase in the average pretest score of 42.85 to 85.14 at the time of the posttest and the results of the n gain test obtained <g> a gain value of 0.74 with a high category. Based on the results of the distributed response questionnaire, a very positive response was obtained from teachers and students. Based on these results, it can be concluded that the Kakasibook learning media is effective in improving learning outcomes in science subjects and is feasible and practical to be applied in student learning.